Effects of Laminate Arrangement on the Failure Behaviour of Hybrid Composite Plates under Transverse Sinusoidal Load - Ab Ghani, Ahmad Fuad; Samsudin, Azizul Hakim; Mohd Sharom, Shaheera Diana; Lu, Yongtao; Mahmud, Jamaluddin (International journal on advanced science, engineering and information technology, 2019)
The present work deals with the effects of laminate arrangement on the failure behaviour of hybrid composite plates under transverse sinusoidal load. Failure analysis has been a subject under study for many years, especially for composite materials. This is largely due to the spontaneous nature of composite materials when it fails without warning. Hybrid composite are commonly utilized to improve the unexpected and instantaneous failure mode of composites. Nevertheless, the failure behaviour of hybrid composites is still not well understood. Moreover, studies have not exploited the effects on sinusoidal transverse loading on hybrid composites. Therefore, the first and last ply failure of the hybrid composite laminate was simulated and analysed using built in failure criteria function in ANSYS. The hybrid composite consisted of graphite (GR) and glass (GL), with lamination schemes of [GL/GL/GL/GL], [GL/GL/GL/GR] and [GR/GL/GL/GL] were subjected of transverse sinusoidal loading.  The laminate failure was predicted using the Maximum Stress Theory. Prior to determining the first and last ply failure of the hybrid composite plate, numerical validation was conducted to ensure the accuracy of the finite element software. The failure curves of the first ply failure and last ply failure were plotted and the results showed significant difference in the correlation of loadings that caused first and last ply failures and the lamination scheme of the hybrid composite plates. Thus, it can be said that the present work proves to be of importance and valuable in the field of study as well as enriching the knowledge regarding the failure behaviour of hybrid composite plate under transverse sinusoidal load of different laminate arrangement.